CHEMISTRY OF KORNERUPINE AND ASSOCIATED MINERALS, A WET CHEMICAL, ION MICROPROBE, AND X-RAY STUDY EMPHASIZING LI, BE, B AND F CONTENTS - Grew E.S.; Chernosky J.V.; Werding G.; Abraham K.; Marquez N.; Hinthorne J.R. (My University, 1990)
Kornerupine and associated minerals in 31 samples of high-grade rocks relatively rich in Al and Mg were analysed by wet chemistry, ion microprobe mass analyser, electron microprobe and X-ray powder diffraction. For 11 samples of kornerupine and three samples of biotite (F only) analysed by both wet chemical and ion microprobe methods, the best agreement was obtained for B 2O 3, whereas the ion microprobe Li 2O values were systematically somewhat higher than the wet chemical values. The wet chemical methods give Li 2O=0-0·19 wt.%; BeO=0-0·032 wt.%; B 2O 3=0-4·01 wt.%; and F=0·07-0·77 wt.% in kornerupine, whereas ion microprobe analyses on other kornerupines give values up to 0·35 wt.% Li 2O, O066 wt.% BeO, and 4·72 wt.% B 2O 3. The sum B+Al+Fe 3++Cr is close to 6·9 atoms per 22 (O, OH, F) or 21·5 (O) in kornerupine.In general, Li/Fe ratios decrease as follows: kornerupine »sapphirine>biotite > Crd (Na<0·03 per 18 oxygens)>tourmaline, garnet, orthopyroxene. However, for cordierite with Na>004, Li/Fe decreases as follows: cordierite>kornerupine. Sapphirine and sillimanite are the only associated minerals to incorporate significant boron (0·1-0·85 wt.% B 2O 3) and then only when the single site for B in kornerupine is approaching capacity. Sillimanite B 2O 3 contents increase regularly with kornerupine F. Fractionation of fluorine increases as follows: kornerupine<biotite<tourmaline, and K krn-BtD=(F/OH) Krn/(F/(OH) Bt (assuming ideal anion composition) increases with biotite Ti. Kornerupine B 2O 3 content is a measure of B 2O 3 activity in associated metamorphic fluid, whereas sillimanite B 2O 3 content increases with temperature, exceeding 0·4 wt.% whenT=900°C at very low water activities.New data on 11 kornerupines and literature data indicate that the unit cell parameters a, c, and V decrease with increasing B content and b, c, and V increase with increasing Fe 3+ content. In Fe 3+-poor kornerupines, b increases with Mg and with (Mg + Fe 2+) but the effect of Mg on b via the substitution VIMg+ IVSi= VIAl+ IVAl overwhelms the effect of Fe 2+=Mg substitution.